QUALITY CULTURE TO IMPROVE KNOWLEDGE SHARING AND THE POSITIVE EFFECT ON ENGAGEMENT OF ACADEMIC STAFF : (An Empirical Study in Indonesian Private Higher Education) - Herminingsih, Anik; Rizki, Mochammad (Archives of Business Research, 2021)
The Ministry of Research, Technology, and Higher Education has a vision that contains the quality of higher education, by quality assurance implementation that aims to build a quality culture of higher education. Quality culture is an organizational value system that produces a conducive environment for the formation and continuous improvement of quality. The effects of quality culture on employee behaviors had been gained researchers attention, and as important factors for fostering knowledge sharing behaviors. This study conducted at Universitas Mercu Buana with 144 lecturers as samples. Data analysis by structural equation model and processed with AMOS software. The result of this study showed that quality culture affected positively human resource management practices, knowledge sharing among lecturers, then affected lecturer' engagement